Pengaruh Model CIRC (Cooperative Integrated Reading and Composition) Terhadap Kemampuan Membaca Pemahaman Siswa Kelas V Madrasah Ibtidaiyah - Arisqa, Windi Putri; Anas, Nirwana (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Reading comprehension is a crucial skill that significantly contributes to students’ academic success across various subjects. However, based on initial observations at MIS Miftahul Fallah Diski, it was found that many fifth-grade students still struggle to understand the content of reading materials, particularly in identifying main ideas and answering questions accurately. This study examines the effect of the Cooperative Integrated Reading and Composition (CIRC) model on the reading comprehension skills of fifth-grade students. The research used a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 20 students selected through purposive sampling. The research instrument was an essay test that had been validated, and the data were analyzed using the Paired Sample t-test with SPSS version 25. The results showed an improvement in the average score from 43.55 on the pretest to 84 on the posttest, with a significance value of 0.000 (p < 0.05). These findings suggest that the CIRC model has a substantial impact on enhancing students’ reading comprehension skills. This study suggests that teachers should consider applying cooperative learning models, such as CIRC, in teaching Indonesian, particularly when focusing on materials that emphasize reading comprehension. Thus, this model can be an effective teaching strategy to create an active, interactive, and collaborative learning environment at the elementary school level.